Biological variation estimates of prothrombin time, activated partial thromboplastin time, and fibrinogen in 28 healthy individuals. (20th August 2018) - Falay, Mesude; Senes, Mehmet; Korkmaz, Selcuk; Turhan, Turan; Okay, Murat; Öztürk, Berna Afacan; Yücel, Doğan; Ozet, Gulsum
Abstract: Background: Although tests of global hemostasis prothrombin time (PT) and activated partial thromboplastin time (aPTT) should not be used for prediction of bleeding risk, these tests are often used by many clinicians in daily practice particularly as a preoperative screening test. Robust biological variation (BV) data are needed for safe clinical applications of these tests. In this study, a stringent protocol was followed to estimate the BV's for PT, aPTT, and fibrinogen levels. Methods: Weekly blood samples were obtained from 28 healthy individuals (18 females, 10 males) during 10 weeks study period. All measurements were performed with Stago STA‐R coagulation analyzer. Prior to coefficient of variation (CV)‐analysis of variance (ANOVA), the data were assessed for normality, trends, outliers, and variance homogeneity. Sex‐stratified within‐individual (CVI ) and between‐individual (CVG ) BV estimates were determined for PT, aPTT, and fibrinogen tests. Results: No difference was found between male and female estimates of BV. The observed CVI and CVG estimates were found to be lower than those previously published. Only for fibrinogen, CVI was higher than CVG . Conclusion: Following a meticulous protocol, our study results provide up‐to‐date and more stringent BV estimates of global hemostasis tests.